PLURALISME DAN MULTIKULTURALISME DALAM PENDIDIKAN ISLAM - Mangunsong, Irvan (STIT Hamzah Al Fansuri, 2024)
Indonesia consists of a plural and multicultural society. Indonesia is rich in diversity in terms of ethnicity, culture, language, ethnicity and religion. However, it is not uncommon for this diversity to cause significant conflict. For this reason, there needs to be a serious effort to educate pluralistic communities about the importance of knowing, respecting and recognizing the existence of a culture or religion. Education about pluralism and multiculturalism is very important today. Of course, in Islamic education, pluralism and multiculturalism become a separate study on how Islam views these two terms and how the application of Islamic values in a multiculturalism environment, Islamic education in shaping multiculturalism values, and Islamic education values about multiculturalism. The author conducts research to answer these questions by using the library research method. The author concludes that Islam supports the concept of pluralism and multiculturalism. Not only supporting, Islam even provides values about multiculturalism and has been applied by the Prophet in a plural environment in Mecca and Medina.